How to Signify Otherness and Diasporic Bodies through Puppetry: Two Plays by Kossi Efoui - (:unkn) unknown (My University, 2023)
Author of various theater plays, French-speaking writer of Togolese origin Kossi Efoui transfers in his texts, relying on the puppet's medium, his experience of political exile from his native country and statelessness, as well as search for an identity in his adoptive country, France. Reluctant to embrace a Western view that tends to relegate authors of African origins to an exotic aesthetic, Kossi Efoui puts a complex concept of identity at the center of his dramaturgy. This chapter is centered on two different texts by Kossi Efoui, "Io (tragédie)" (2006) and "En guise de divertissement" (2013). The latter was conceived as a stage writing together with the puppet theater company Théâtre Inutile, during a collaboration lasting twenty years. Analyzing the two texts, I aim to demonstrate how the basic themes of Efoui's dramaturgy-the trauma of exile and the expropriation, on the one hand, and the rehabilitation of a human feeling, of one's own history and identity, on the other-find their best concretization in the staging carried out with puppets.
Keywords: African Research